KONTRIBUSI PEMAHAMAN KOSAKATA BIDANG JURNALISTIK TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 22 PADANG - Yonafri, Cindy; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT There are three objectives of this research. First, describing the comprehension of journalistic vocabulary  at students grade VIII SMP Negeri 22 Padang. Second, describing the  writing skill of  news text at student grade VIII SMP Negeri 22 Padang. Third, describing the contribution of journalistic vocabulary towards the skill in writing news text at students grade VIII SMP Negeri 22 Padang. This is a quantitative research with descriptive method and using correlational research design. Population and sample of this research are VIII th grade student of SMP Negeri 22 Padang consist of 223 students and 44 sample students. This research use Simple Random Sampling technique. This experiment consists of two variables: vocabulary as the independent variable (X) and the writing skills of news text as a dependent variable (Y). Based of result data analyze and explanation, were concluded 3 case. First, comprehension of journalistic vocabulary on students grade at VIII  SMP Negeri 22 Padang  was on good qualification (83,88). Second, writing skills of news text  at students grade VIII SMP  Negeri 22 Padang was on good qualification (81,91). Third,  comprehension  vocabulary on environment  areacontributed toward writing skills news text  at students grade VIII  SMP Negeri 22 Padang. Nevertheless, for the writing skills news text were needed comprehension of vocabulary on journalistic. Kata kunci : Kontribusi, Penguasaan Kosakata Bidang Jurnalistik, Keterampilan Menulis Teks Berita